Green synthesis of magnetic 3D bio-adsorbent by corn straw core and chitosan for methylene blue removal. Issue 16 (15th July 2020) - Liu, Shanshan; Ge, Heyi; Cheng, Shilin; Zou, Yu
ABSTRACT: In this work, a novel bio-adsorbent with a unique structure was prepared through one-step crosslinking in the emulsion using corn straw core (CSC), CoFe2 O4 and chitosan (CS) as raw materials for adsorption of methylene blue (MB). The preparation method of the adsorbent was simple and environmentally friendly. In the adsorbent, the agricultural waste of CSC acted as scaffold and was wrapped with CS. CoFe2 O4 was embedded in CS, giving magnetic property to the adsorbent, which was beneficial to the separation process. XRD, FTIR, SEM and TEM were utilized to characterize the adsorbent and the factors affecting adsorption removal efficiency were explored. The pseudo-second-order model and the Langmuir model described the adsorption behaviour well. The equilibrium adsorption capacity was 122 mg g −1 for MB at 298 K. The thermodynamic studies suggested that the adsorption was a spontaneous, exothermic and randomness decrease process. MB loaded on the adsorbent could be desorbed by immersing in dilute acid solution, indicating that this kind of biomass adsorbent can be widely used in the field of adsorption. GRAPHICAL ABSTRACT: